1984
DOI: 10.1073/pnas.81.3.903
|View full text |Cite
|
Sign up to set email alerts
|

12S,20-dihydroxyicosatetraenoic acid: a new icosanoid synthesized by neutrophils from 12S-hydroxyicosatetraenoic acid produced by thrombin- or collagen-stimulated platelets.

Abstract: A new metabolite of arachidonic acid, formed during interaction between thrombin-or collagenstimulated platelets and unstimulated neutrophils, has been demonstrated by both thin-layer radiochromatography and high-performance liquid chromatography. Production of the 3H-labeled metabolite in combined suspensions containing[3H]arachidonate-labeled platelets and unlabeled neutrophils from aspirin-treated donors suggested that platelet 3H-labeled 12S-hydroxy-5,8-cis,10-trans,14-cis-icosatetraenoic acid (12-HETE) wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
37
0

Year Published

1990
1990
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 127 publications
(40 citation statements)
references
References 11 publications
3
37
0
Order By: Relevance
“…It was also demonstrated that PMNL stimulated with the ionophore A23187 in the presence of platelets transform platelet-derived 12S-hydroxy-5, 8,10,14-(Z,Z,E,Z)-eicosatetraenoic acid (12-HETE) into 5S,12S-dihydroxy-6,8,10,14(E,Z,E,Z)-eicosatetraenoic acid (5S, 12S-DiHETE) Marcus et al, 1982), and arachidonic acid into LTB4 (Marcus et al, 1982) via the 5-lipoxygenase pathway. In addition, 12-HETE synthesized in platelets is metabolized to 12S,8,10,14(Z,Z,E, by unstimulated neutrophils (Marcus et al, 1984). In previous studies we have also shown that incubation of PMNL with high concentration of exogenous arachidonic acid in the presence of platelelets results in increased synthesis of 5-lipoxygenase products.…”
Section: Introductionmentioning
confidence: 79%
See 1 more Smart Citation
“…It was also demonstrated that PMNL stimulated with the ionophore A23187 in the presence of platelets transform platelet-derived 12S-hydroxy-5, 8,10,14-(Z,Z,E,Z)-eicosatetraenoic acid (12-HETE) into 5S,12S-dihydroxy-6,8,10,14(E,Z,E,Z)-eicosatetraenoic acid (5S, 12S-DiHETE) Marcus et al, 1982), and arachidonic acid into LTB4 (Marcus et al, 1982) via the 5-lipoxygenase pathway. In addition, 12-HETE synthesized in platelets is metabolized to 12S,8,10,14(Z,Z,E, by unstimulated neutrophils (Marcus et al, 1984). In previous studies we have also shown that incubation of PMNL with high concentration of exogenous arachidonic acid in the presence of platelelets results in increased synthesis of 5-lipoxygenase products.…”
Section: Introductionmentioning
confidence: 79%
“…Figure 1 shows that activated platelet and PMNL mixtures produced 55,12S-DiHETE, which is a product of the double dioxygenation of arachidonic acid by the 5-and 12-lipoxygenases Marcus et al, 1982). The product of the co-oxidation of the 5S,12S-DiHETE in the PMNL, the 5S,12S,20-TriHETE (Lindgren et al, 1981), was always formed in substantial amounts, while the 12-HETE metabolite, 12,20-DiHETE (Marcus et al, 1984) was also present but in smaller amounts. The mechanism of formation of these three products of platelet-PMNL interaction have been discussed previously (Lindgren et al, 1981;Marcus et al, 1987).…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, it is likely that lipoxygenase metabolites are involved in plateletmediated leucopenia following antigen challenge. It has been established that platelets possess a lipoxygenase which transforms the unstable metabolite 12-hydroperoxy-eicosatbtraenoic acid (12-HPETE) into 12-hydroxyeicosatetraenoic acid (12-HETE), the latter being a chemotactic agent for neutrophils and eosinophils (Marcus et al, 1984). In addition, the coincubation of platelets and leucocytes in the presence of arachidonic acid induced the release of 12-HPETE from platelets which, in turn, activated the 5-lipoxygenase of leucocytes leading to the production of 5-HETE (Maclouf et al, 1982).…”
Section: Discussionmentioning
confidence: 99%
“…3A). These reactions will generate chain-shortened metabolites, such as tetranor-12(R)-HETE [8(R)-HHxTrE], or -hydroxylated metabolites such as 12(R), 20-DiHETE, respectively (Marcus et al, 1984;Gordon et al, 1989). An additional metabolic pathway involving oxidation of 12-HETE to a keto intermediate (12-oxo-ETE) followed by keto-reduction to 12(R)-HETrE, a 12(S)HETE analog, has been described in porcine neutrophil and bovine corneal epithelial microsomes (Yamamoto et al, 1994).…”
Section: Metabolites Of 12(r)-hete Fail To Activate Ahrmentioning
confidence: 99%